Legal situation and current practice of waste incineration bottom ash utilisation in Europe. (1st February 2020) - Blasenbauer, Dominik; Huber, Florian; Lederer, Jakob; Quina, Margarida J.; Blanc-Biscarat, Denise; Bogush, Anna; Bontempi, Elza; Blondeau, Julien; Chimenos, Josep Maria; Dahlbo, Helena; Fagerqvist, Johan; Giro-Paloma, Jessica; et al.
Highlights: Overview on regulations regarding bottom ash utilisation in 22 European countries. Diverse regulation of bottom ash utilisation in the EU. Utilisation rates vary between 0% and 100% between investigated countries. Critical discussion of limit values and comparison between countries. Proposal of key-points for a uniform legislation at EU level. Abstract: Almost 500 municipal solid waste incineration plants in the EU, Norway and Switzerland generate about 17.6 Mt/a of incinerator bottom ash (IBA). IBA contains minerals and metals. Metals are mostly separated and sold to the scrap market and minerals are either disposed of in landfills or utilised in the construction sector. Since there is no uniform regulation for IBA utilisation at EU level, countries developed own rules with varying requirements for utilisation. As a result from a cooperation network between European experts an up-to-date overview of documents regulating IBA utilisation is presented. Furthermore, this work highlights the different requirements that have to be considered. Overall, 51 different parameters for the total content and 36 different parameters for the emission by leaching are defined. An analysis of the defined parameter reveals that leaching parameters are significantly more to be considered compared to total content parameters. In order to assess the leaching behaviour nine different leaching tests, including batch tests, up-flow percolation tests and one diffusion test (monolithic materials) are in place. A further discussion of leaching parameters showed that certain countries took over limit values initially defined for landfills for inert waste and adopted them for IBA utilisation. The overall utilisation rate of IBA in construction works is approximately 54 wt%. It is revealed that the rate of utilisation does not necessarily depend on how well regulated IBA utilisation is, but rather seems to be a result of political commitment for IBA recycling and economically interesting circumstances.